ID: 45. Issue 4 (April 2016) - Afroze, SH; Zawieja, DC; Tobin, R; Peddaboina, C; Newell-Rogers, MK; McDowell, AC; McCormick, TC; Kuehl, TJ; Uddin, MN
Abstract : Objective: Cinobufotalin (CINO), a cardiotonic steroid (CTS) or bufadienolide, is extracted from the skin secretions of the traditional Chinese medicine giant toads (Chan su). CINO has been used as a cardiotonic, diuretic and a hemostatic agent. Previously we have shown that CINO inhibits the cytotrophoblast cell function. Recently other study has shown that CINO inhibits A549, a lung cancer cell function. In this study, we assessed the effect of CINO on three different ovarian cancer cell lines; SK-OV-3, CRL-1978 and CRL-11731 to confirm whether the effect of CINO is cell specific. Study Design: We evaluated the effect of CINO on three ovarian cancer cells SK-OV-3, CRL-1978, and CRL-11731 function in vitro. Each Cell lines were treated with different concentrations of CINO (0.1, 1, 5 and 10 µM). For each cell line cell proliferation, migration and invasion were measured by using a CellTiter Assay (Promega), Cytoselect Assay (Cell Biolabs) and by using a FluoroBlock Assay (BD) respectively. Proliferating Cell Nuclear Antigen (PCNA) was also evaluated in cell lysates of CINO treated these 3 ovarian cancer cells by western blot analysis. Cell Cycle arrest and Cell viability were determined by fluorescence-activated cell sorting (FACS) analysis. We also performed Annexin V staining on CINO treated these 3 ovarian cancer cell lines by immunofluorescence to evaluate the pro-apoptotic protein expression. In addition mitochondrial membrane potential has also been measured for all these 3 ovarian cell lines after CINO treatment using MMP kit, by FACS analysis. Results: Concentration of CINO at 0.5 µM inhibit SK-OV-3, CRL-1978, and CRL-11731 ovarian cancer cells proliferation, migration and invasion without cell death and loss of cell viability but cell viability differs for each cell line. Each cell lines differ in response to CINO doses for PCNA expression as well as Annexin V pro-apoptotic protein expression. CINO decreases mitochondrial membrane potential for SK-OV-3 but for CRL-1978 and CRL-11731 increases in response to CINO treatment. Conclusion: CINO is cell specific, as each cancer cell line responds differently. These data demonstrate that the mode of action of CINO is different on these 3 types of ovarian cancer cells.